2017
DOI: 10.14744/nci.2017.27122
|View full text |Cite
|
Sign up to set email alerts
|

The effects of preobesity to quality of life, disease activity and functional status in patients with ankylosing spondylitis

Abstract: OBJECTIVE:This study was an investigation of effects of pre-obesity on clinical characteristics and quality of life in patients with ankylosing spondylitis (AS).METHODS:Total of 28 AS patients and 30 age- and sex-matched healthy controls were included in the study. Patients and controls with any systemic inflammatory disease and/or cognitive and mental problems were excluded. Disease activity and functional capacity were measured using the Bath Ankylosing Spondylitis Disease Activity Index and Bath Ankylosing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 32 publications
1
1
0
Order By: Relevance
“…However, static balance measurements were affected by the disease duration in our study as similar to the literature [23]. To our best knowledge, there is no study investigating the effect of BMI on static balance of AS compared with our study but Toy et al found that increased BMI in patients with AS is a factor that affects the quality of life, disease activity, and functional capacity [24].…”
Section: Discussionsupporting
confidence: 86%
“…However, static balance measurements were affected by the disease duration in our study as similar to the literature [23]. To our best knowledge, there is no study investigating the effect of BMI on static balance of AS compared with our study but Toy et al found that increased BMI in patients with AS is a factor that affects the quality of life, disease activity, and functional capacity [24].…”
Section: Discussionsupporting
confidence: 86%
“…While it is known that a higher BMI correlates with a greater burden of symptoms in patients with AS,35 the role of adiposity in the QoL of patients with AS has not been widely investigated. Toy and colleagues36 reported in their study that while all of the SF-36 QoL criteria were significantly lower in the preobese patients with AS compared with healthy controls, no significant relationships were observed between patients with AS whose BMI was between 27.1 and 29.9 and those whose BMI was in the range of 25–27. The underlying link between low social participation QoL and obesity observed in the present study will require further investigation, in particular whether the relationship is mediated through obesity-related body image dissatisfaction or physical immobility 37.…”
Section: Discussionmentioning
confidence: 88%